부동산 투자에서 관계 품질의 선행요인과 결과요인 - 지성구(Ji, Seong-Goo); 양정연(Yang, Jeong-Yeon) (대한경영학회지, 2007)
최근 들어 기존 고객과의 관계증진에 대한 관심이 높아짐에 따라 기업과 고객의 관계마케팅에 대한 중요성이 높아지고 있다. 그러나 부동산 투자고객과 투자회사간의 관계마케팅은 학문적으로 소홀하게 다루어졌다. 이에 본 연구에서는 부동산 투자회사들이 부동산 투자고객과의 장기적 관계를 증진하기 위해 핵심요소라 할 수 있는 관계품질의 선행요인과 결과변수를 규명하고자 하였다. 부동산 투자회사를 통해 투자경험이 있는 고객 345명을 대상으로 분석한 결과, 호감성, 전문성, 고객지향성은 판매원신뢰에 정의 영향을 미치고, 평판, 상호작용, 투자상품은 투자회사신뢰에 정의 영향을 미치는 것으로 나타났다. 또한 판매원신뢰는 투자회사 신뢰에 정의 영향을 미치고, 이러한 신뢰는 몰입과 재투자의도에 정의 영향을 미치는 것으로 나타났다. 끝으로, 연구의 시사점을 제시하고, 한계점과 미래 연구방향을 제시하였다. The purpose of this study is to examine the antecedents influencing relationship quality in determining intent-to-reinvest by existing clients of real-estate investment companies and provide administrative suggestions in reinvestment strategies. We performed covariance structural analysis based on 345 subjects on clients of real-estate investment development companies. The results showed that perceived favor, expertise, and customer orientation of salespeople have positively influenced on customer trust. And, reputation, interaction and investment products of investment companies showed to be antecedent factors in trust towards investment development companies. In addition, trust positively affected commitment and commitment positively affected intent-to-reinvest. Finally, we discuss the results of analysis and suggest research limitation and future study. KCI Citation Count: 1